Offshore Wind Policy in Portugal Balancing Green Growth and Legal Equity - Vaz, Ramalho-Santos; Neave, Silveirinha; Branco, Pillinger Castelo (International Journal of Law and Public Policy (IJLAPP), 2025)
Portugal's ambitious plan to expand offshore wind capacity to 10 GW by 2030 positions the country as a frontrunner in Europe’s green energy transition. However, this rapid development raises pressing legal and policy challenges concerning environmental justice, public accountability, and governance. This study critically examines the legal framework and regulatory instruments that govern offshore wind projects in Portugal, particularly focusing on spatial planning, licensing procedures, and mechanisms of public participation. Using a doctrinal legal research method combined with policy analysis, this paper analyzes national legislation, EU directives, and recent regulatory practices, while integrating cases of contestation from coastal communities and environmental organizations. The findings reveal significant procedural gaps in public participation, particularly the exclusion of local fishing communities and municipal stakeholders from the zoning and licensing processes. Moreover, the current auction-based model privileges investment logic over environmental and social equity. The lack of independent environmental assessments and weak grievance mechanisms raise concerns about transparency, legal accountability, and compliance with the Aarhus Convention principles. This study argues that Portugal’s offshore wind transition, while environmentally progressive in ambition, requires stronger legal safeguards to ensure that it is also socially just and participatory. Recommendations are offered to improve the governance architecture toward a more inclusive and equitable energy policy.